The laughing mask - Aguiar, Michael; Jenkings, Jeff; Hardy, John (Actor); Rivers, Sheyenne; Lee, Gabriel; Pendragon Pictures; Leomark Studios (Firm) ([United States] : Pendragon Pictures, 2014)
A grisly murder perpetrated by a deranged killer, Jake Johnson's wife and daughter were murdered by a Psychotic vigilante only known as The Laughing Mask. As the police look for clues and the body count begins to rise, Johnson will play a dangerous game in order to avenge his family's death.
Originally released as a motion picture in 2014
John Hardy, Sheyenne Rivers, Gabriel Lee, Jeff Jenkings (the Laughing Mask), Fran Rafferty, Amanda Pierre, Terence Van Auken, Matt Ganey, Haley Mikenas.
Cinematographer, William Schweikert ; editors, David Lopez, Michael Aguiar, Kyle Fritsche ; composers, Greg Rosetti, Rich Giaimo.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 8, 2017).
Keywords: Murder -- Drama; Revenge -- Drama; Horror films; Feature films; Fiction films; Internet videos; Streaming video